Pengaruh Jumlah Uang Elektronik yang Beredar di Masyarakat Terhadap Pertumbuhan Ekonomi Indonesia - Saidah, Zumi; Siregar, Rini Natalia; Elwinda, Derifa Shafa; Ramahani, Cinta; Damanik, Marisa (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Economic growth is a value that shows the level of production of goods and services achieved by a country so that it can reflect the state of the country's economy. Payments using non-cash or frequently used money such as electronic money are considered more efficient and economical, so the value of electronic money transactions increases every year. This research analyzes the influence of the value of electronic money transactions, money supply and inflation on Indonesia's economic growth, in this case GDP. Secondary data from 2018 to 2022. The data analysis method used is multiple linear regression. From the results of the tests that have been carried out, values were foundelectronic money transactions, money supply (JUB), and inflation has a significant effect on economic growth in Indonesia. The higher the value of electronic money transactions and inflation can increase economic growth, but the greater the money supply, the lower economic growth (GDP).